Sensitivity of Influenza Rapid Diagnostic Tests to H5N1 and 2009 Pandemic H1N1 Viruses - Sakai-Tagawa, Yuko; Ozawa, Makoto; Tamura, Daisuke; Le, Mai thi Quynh; Nidom, Chairul A; Sugaya, Norio; Kawaoka, Yoshihiro (Journal of Clinical Microbiology, 2010)
Simple and rapid diagnosis of influenza is useful for making treatment decisions in the clinical setting. Although many influenza rapid diagnostic tests (IRDTs) are available for the detection of seasonal influenza virus infections, their sensitivity for other viruses, such as H5N1 viruses and the recently emerged swine origin pandemic (H1N1) 2009 virus, remains largely unknown. Here, we examined the sensitivity of 20 IRDTs to various influenza virus strains, including H5N1 and 2009 pandemic H1N1 viruses. Our results indicate that the detection sensitivity to swine origin H1N1 viruses varies widely among IRDTs, with some tests lacking sufficient sensitivity to detect the early stages of infection when the virus load is low.